Preventing disease in the 21st century: early breast milk exposure and later cardiovascular health in premature infants - El-Khuffash, A; Jain, A; Lewandowski, A; Levy, P (Springer Nature, 2019)
Cardiovascular health of premature infants reaching early adulthood is an area of ongoing research. There is emerging evidence delineating the challenges faced by those individuals. Young adults born premature demonstrate a unique cardiac phenotype characterized by reduced biventricular volume, relatively lower systolic and diastolic function, and a disproportionate increase in muscle mass. This may clinically manifest by an increased risk of cardiovascular incidents, hypertension, and reduced exercise tolerance. Those consequences appear to result from early postnatal cardiac remodeling due to premature birth and associated co-morbidities. Recent evidence suggests that early exposure to breast milk slows down or even arrests those pathophysiological changes, thereby mitigating the long-term adverse effects of premature birth on cardiovascular health. In this review article, we discuss the role of breast milk in preventing early adulthood cardiovascular disease in infants born premature. We explore the emerging evidence and examine the possible mechanistic pathways mediating this phenomenon. Furthermore, we aim to demonstrate the vital role of early breast milk exposure in preventing cardiovascular disease in preterm infants.